2016
DOI: 10.1097/coh.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

Do people with HIV infection have a higher risk of fracture compared with those without HIV infection?

Abstract: This review examines data from recent cohort studies and clinical trials to inform a better understanding of the complex relationship between the effects of HIV infection, ART and demographics on fractures in PLWH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Whether ART increases fracture risk is unclear, with contradictory results reported from multiple studies. The effect of ART is likely small in women under the age of 50 years and men under 60 years . The young age of our study population may have contributed to the low rate of fractures and lack of treatment group difference…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Whether ART increases fracture risk is unclear, with contradictory results reported from multiple studies. The effect of ART is likely small in women under the age of 50 years and men under 60 years . The young age of our study population may have contributed to the low rate of fractures and lack of treatment group difference…”
Section: Discussionmentioning
confidence: 94%
“…The effect of ART is likely small in women under the age of 50 years and men under 60 years. (39) The young age of our study population may have contributed to the low rate of fractures and lack of treatment group difference. (14) There was no independent association between baseline CD4 count and change in BMD in the immediate ART group.…”
Section: Discussionmentioning
confidence: 99%
“…Further parameters included an echo time TE =4.2 ms, readout bandwidth rBW =±62.5 kHz, repetition time TR =10 ms and a flip angle α =60°. A spatial resolution of 234×234×500 µm 3 was achieved in approximately 15 minutes of acquisition time. Automatic coil correction by nonparametric nonuniform intensity normalization (N3) (24) was applied to all MR scans.…”
Section: Mri and Image Analysismentioning
confidence: 99%
“…[2][3][4][5] HIV-related osteoporosis and osteomalacia occur relatively frequently and put patients at risk for fractures at a rather young age. 6,7 Recent estimations of the prevalence of osteopenia and osteoporosis in HIV + individuals range from 48% to 52% and from 10% to 23%, respectively. [8][9][10] Prospective and retrospective studies have demonstrated decreases in bone mineral density (BMD) of 2%-6% in the first 2 years after the start of cART, depending on the type of cART.…”
Section: Introductionmentioning
confidence: 99%